Evaluating the impacts of color, graphics, and architectural features on wayfinding in healthcare settings using EEG data and virtual response testing. (February 2022) - Kalantari, Saleh; Tripathi, Vidushi; Kan, Julia; Rounds, James D.; Mostafavi, Armin; Snell, Robin; Cruz-Garza, Jesus G.
Abstract: Wayfinding difficulties in healthcare facilities have been shown to increase anxiety among patients and visitors, to reduce staff operational efficiency, and to increase operational costs. There is evidence that wayfinding-oriented interior design features can mitigate these problems, but the robust evaluation of wayfinding design strategies is hindered by the unique nature of each building and the expense of testing different navigational aids. The current study implemented a novel testing approach using virtual reality and EEG data to evaluate the effects of three different interior designs, using altered color patterns, graphics, and architectural features intended to enhance wayfinding in a specific hospital facility. Multiple sources of data including self-reported responses, behavioral metrics, and measurements of neural activity in wayfinding-relevant brain regions were collected. The results indicated that the most extensive wayfinding design was associated with improvements in some orientation behaviors and with greater neurological activation in the brain regions of interest. However, these findings did not translate into improved wayfinding times or reductions in self-reported stress, fatigue, or confusion. The authors discuss the implications of these findings and make extensive recommendations for the future directions of evidence-based pre-construction design testing. The streamlined testing platform and data-analysis approach that was developed in this work can make this evidence-based approach more feasible for other researchers and professional designers, eventually leading to a broad comparative data-set incorporating a wide range of buildings and participants. Highlights: Distinct design conditions tested in immersive virtual reality hospital environment. Enhanced signage and environmental affordances improve wayfinding efficacy. Mobile EEG neural dynamics of wayfinding in visual association area. Beta band (13–30 Hz) desynchronization with enhanced environmental affordances. Theta band (4–7 Hz) desynchronization with enhanced signage.